Beyond poverty alleviation: National Rural Livelihoods Mission’s contribution to gender transformation and women’s economic empowerment in Jammu and Kashmir, India - Neer Somakka, A.N.; Dwivedi, Sudhakar (Sher-e-Kashmir University of Agricultural Sciences and Technology, 2023)
The programs of the National Rural Livelihood Mission (NRLM) in Jammu and Kashmir, India, cater to around 80,371 self-help groups (SHGs) with 639,140 members. NRLM is a government initiative aimed at improving the economic well-being of rural women by promoting the formation of SHGs and providing them with access to financial services and support. In this study, the focus was on understanding how participation in the program affected the income of women in the region. A total of 303 women from 143 self-help groups were studied as treatment groups, and 120 below-poverty-line women from the same village were studied as control group. We followed the steps mentioned in Caliendo and Kopeinig for using the propensity score matching technique which compares the treatment and control groups in observational studies to estimate causal effects. The study’s results indicated that the treated group, which had participated in the program, had a significantly higher mean income compared to the control group, suggesting that the treatment group was significantly more likely to have access to financial services than the control group. The average income of the treated group is Rs.6324.422, while the average income of the control group is Rs.5051.703. This means that the treatment is increasing income by an average of Rs.1272.719. The findings indicate that participation in the program had a positive and statistically significant effect on women’s income, demonstrating the program’s effectiveness in improving the economic well-being of rural women in the region.